Statement of Removal—Retention of graduate trainee programmes: a case study of Hilton's Elevator fast-track to general manager graduate programme (Research in Hospitality Management)
This article has been removed in accordance with the journal's editorial policies.Article title: Retention of graduate trainee programmes: a case study of Hilton's Elevator fast-track to general manager graduate programmeAuthors: Florentina Enachi, Javed Suleri & Edwin TarusJournal: Research in Hospitality ManagementCitation information: 2023, 13(3): 143-151Version of Record published online: 07 March 2024DOI: https://doi.org/10.1080/22243534.2024.2322221© 2025 The Authors